PENGARUH SALES PROMOTION, STORE ATMOSPHERE DAN POSITIF EMOTION TERHADAP IMPULSE BUYING (E-logis : Jurnal Ekonomi Logistik, 2021)
The increasingly fierce competition of batik clothing stores in Semarang today, requires companies to always pay attention to the needs and desires of consumers and try to meet consumer expectations by having a good sales promotion program, creating a good store atmosphere and creating positive emotion (positive emotions) then will be more interested in making purchases at the store so that impulse buying is created. This study aims to determine and analyze the effect of sales promotion, store atmosphere, and positive emotion on impulse buying. The population in this study were all customers of the Batik Maris Batik Shop in Gajah Mada Semarang from October 2019 to November 2019 whose numbers were not known with certainty. The number of samples used in this study were 100 respondents. The sampling technique is purposive sampling. The analytical tool used is multiple regression and hypothesis testing. Based on the results of data analysis it can be concluded; (1) There is a significant influence between Sales Promotion on Impulse Buying, (2) There is a significant influence between Store Atmosphere on Impulse Buying, (3) There is a significant influence between Positive Emotion on Impulse Buying, (4) and There is a significant influence between Sales Promotion, Store Atmosphere, and Positive Emotion for Impulse Buying simultaneously.